The Determinants of Interest Rate Derivatives Use: Evidence from UK Non-Financial Firms. - Tran, Thanh Binh (2016)
This study employs a large sample of 301 UK non-financial companies for 11 years from 2005 to 2015 to clarify the determinants of interest rate derivatives use with hedging data uniquely collected from firms’ annual reports. Results from logit regressions suggest that the majority of hypotheses under optimal hedging theory are valid for firm’s decision of hedging by interest rate derivatives. In which, firms with larger size, higher expected costs of financial insolvency, lower liquidity are more likely to take derivative positions. Robustness test with the exclusion of other derivative users from IR derivative users and non-users group. The regression estimates show little difference to ones before robustness tests except tax losses dummy variable which turns out to be positively significant. Other tests for determinants of the extent of using derivatives by tobit and two-part models reach mixed results of the impacts of economies of scale on firm’s decision to extensively hedge with IR derivatives.